Nursing in Critical Care Setting An Overview from Basic to Sensitive Outcomes - Comisso, Irene (Springer International Publishing, 2018)
This book provides essential insights into how the approach to nursing care in ICU patients has markedly changed over recent years. It shows how the focus has progressively moved away from the technical approach that characterized early ICUs to a wider personalization of patient care that also highlights general problems such as basic hygiene and general comfort. It also demonstrates that, at the same time, the nurses' role has become more professionalized, with increasing competences in assessing and managing patients' problems and measuring related outcomes. It is structured in four units: Unit 1 presents the essential elements of accurate vital-function and basic-needs assessments for ICU patients, using both instrumental monitoring and specially validated assessment tools. Unit 2 addresses basic care in ICU patients, particularly hygiene and mobilization, reflecting recent developments in nursing that focus on the importance of these activities. Unit 3 highlights the main nursing outcomes in ICU patients, particularly focusing on risk prevention and complication management. Lastly, Unit 4 discusses advances in ICU nursing, from clinical, organizational and research perspectives.